Disciplinary Variations in Framing Research Articles in the Social Sciences and Humanities - Yuvayapan, Fatma; Yakut, Ilyas (English Studies at NBU, 2023)
Metadiscourse is now a widely used term in academic discourse analysis. How academics employ rhetorical devices to structure their texts, establish reader-writer interaction and stamp their authorial stance regarding the conventions of the disciplines, cultures, and genres has been the subject of many studies. Despite the growing prominence of the term, however, some features of it, one of which is frame markers, have gone unnoticed. Frame markers signal the boundaries in the academic discourse for the readers' understanding, and they are a crucial rhetorical feature of metadiscourse. The present study examines the deployment of frame markers in research articles written between 2010 and 2019. Based on the analysis of frame markers in a corpus of research articles across four disciplines in social sciences, there were marked variations across the four disciplines in the use of frame markers and the occurrences of their sub-categories. The findings suggested that academic communities have a decisive role in constructing text structures in research articles. The results might offer guidance to academic writers on shaping the texts that their readers find persuasive.